1825 N.H. Laws 74, § 5 - (:unkn) unknown (My University, 1825)
An Act to Regulate the Keeping and Selling, and Transporting of Gunpowder, § 5: Banned sale or offer for sale by retail any gunpowder in any highway, or in any street, lane, or alley, or on any wharf, or on parade or common.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER